The concept of religious character education according to the perspective of K.H. Abdullah said for students - Abdul Halim Muhammad; Dede Rosyada; Dimyati; Suwendi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to analyze the concept of religious character education proposed by K.H. Abdullah Said and its implementation at the Hidayatullah Islamic Boarding School in Balikpapan. Employing a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that religious character education is grounded in tawhid as an epistemological foundation shaping students’ worldview, value orientation, and behavior in an integrated manner. The Systematics of Revelation functions as an educational manhaj that structures the internalization of values progressively, from spiritual awareness to social responsibility. The study also reveals the integration of the formal curriculum and hidden curriculum as a key factor in character formation, while identifying a gap between students’ conceptual understanding of religious values and their behavioral consistency. This research contributes to Islamic character education studies by offering a holistic, tawhid-based educational model that is contextually rooted and responsive to contemporary educational challenges.